Alternative Dispute Resolution (ADR) Hybrid in Cameroon as a Form of Legal Protection for Consumers of Defective Products - Amandong, Egute Matthew (Faculty of Law, Universitas Brawijaya, 2021)
As part of the awareness creation exercise, this paper seeks to establish that consumers of defective products in Cameroon should be exposed to the various extra-judicial channels once they can be adopted by Government and through which the consumers can enforce their rights. This is known as Alternative Dispute Resolution (ADR). The acronym ADR is a group of flexible approaches which could be applied in resolving disputes related to defective products more quickly and at a lower cost than going through the tedious road of adversarial proceedings. ADR mechanisms generally are intended to mean alternatives to the traditional court process. Their adoption will involve the use of impartial interveners who are referred to as